Molecular Mechanisms of Porphyromonas gingivalis Lipopolysaccharide in Periodontitis Pathogenesis - Maura Kyla Nisafira; Ria Aryani Hayuningtyas (SONDE (Sound of Dentistry), 2025)
Introduction: Periodontitis is a chronic inflammatory disease that leads to progressive destruction of periodontal tissues, ultimately causing tooth loss. The Gram-negative bacterium Porphyromonas gingivalis (P. gingivalis) is a key pathogen in periodontitis, with lipopolysaccharide (LPS) playing a major role in immune modulation and inflammatory responses. This review examines the molecular mechanisms by which P. gingivalis LPS contributes to periodontitis pathogenesis, focusing on immune response, epigenetic modifications, and hypoxia-induced inflammation. Methods: A literature search was conducted using PubMed and Google Scholar to identify studies published in the last 10 years. The search was performed using the keywords 'Porphyromonas gingivalis,' 'lipopolysaccharide,' and 'periodontitis.' Articles were selected based on language (English or Indonesian) and full-text availability. Results and Discussion: P. gingivalis LPS activates Toll-like receptor 4 (TLR4), leading to pro-inflammatory macrophage polarization and cytokine release. It also induces epigenetic modifications, such as DNA methylation reduction and histone acetylation, which sustain inflammation. Additionally, hypoxia amplifies caspase-1 activation, worsening periodontal tissue destruction. Conclusion: The involvement of P. gingivalis LPS in periodontitis suggests that immune dysregulation, epigenetic modifications, and hypoxia-induced inflammation are key drivers of the disease. Targeting LPS-TLR4 interactions and inflammatory pathways may offer new therapeutic strategies for managing periodontitis.